2017
DOI: 10.1093/jtm/tax073
|View full text |Cite
|
Sign up to set email alerts
|

Case report of the patient source of the Babesia microti R1 reference strain and implications for travelers

Abstract: This case provides clinical information about the patient infected with the R1 isolate and a review of travel risk, diagnosis and treatment of babesiosis in endemic and non-endemic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
(102 reference statements)
0
13
0
Order By: Relevance
“…A further consideration in immunoassay development is strain specificity, with antigens that are immunoreactive to antibodies elicited by different strains ideally required for useful diagnosis. The protein library was based on the genome sequence from the B. microti reference strain R1 which was isolated from a human patient thought to have been infected in Nantucket (Stahl et al, 2018); however, the R1 strain genome has been recently shown to represent a different lineage from other clinically relevant strains found in the New England (USA) area (Silva et al, 2016). As LS1 was originally isolated from a rodent, we felt it important to verify immunoreactive immunogens in a clinical isolate.…”
Section: Resultsmentioning
confidence: 99%
“…A further consideration in immunoassay development is strain specificity, with antigens that are immunoreactive to antibodies elicited by different strains ideally required for useful diagnosis. The protein library was based on the genome sequence from the B. microti reference strain R1 which was isolated from a human patient thought to have been infected in Nantucket (Stahl et al, 2018); however, the R1 strain genome has been recently shown to represent a different lineage from other clinically relevant strains found in the New England (USA) area (Silva et al, 2016). As LS1 was originally isolated from a rodent, we felt it important to verify immunoreactive immunogens in a clinical isolate.…”
Section: Resultsmentioning
confidence: 99%
“…However, he had traveled to Cape Cod, Massachusetts, an endemic area of Ixodes tick carrying Babesia microti, which allowed us to narrow down the differential between numerous tick-borne illnesses such as Lyme disease, Rocky Mountain spotted fever, and ehrlichiosis [3]. A case report by Stahl et al [4] required polymerase-chain-reaction (PRC), whereas in our patient, we were able to see the pathognomonic maltese cross on PBS (Figure 2), to make the final diagnosis of babesiosis. Currently in high-risk patients (asplenic or immunocompromised) such as ours, current treatment consists of atovaquone and azithromycin or clindamycin.…”
Section: Discussionmentioning
confidence: 99%
“…Infections with Babesia microti have been on the rise in the last couple of years [ 2 ]. National notifiable parameters added Babesiosis to the National Notifiable Conditions in 2011 which made the documentation of the disease further recognizable [ 2 - 4 ]. Although babesiosis is not considered a significant health concern in Florida, it was designated a reportable disease in 2017 in the state [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations